Визуализирующая способность динамических симуляций - Лаврова, К. А. (БНТУ, 2022)
The history of the development of dynamic simulations was considered, their iconic examples from the field of art were given. A website was presented with author's examples of dynamic simulations in 5 categories (dynamics of gases, liquids, soft, rigid bodies and other).